ANALISIS KEMAMPUAN MENULIS PUISI SISWA KELAS V SD NEGERI 63 PEKANBARU - Irawati, Desi; Kurniaman, Otang; antosa, zairul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research background of the low ability to write poetry fifth grade students at SDN 63 Pekanbaru caused by the complexity of the problems that exist in the writing activity and less skilled students in expressing the idea that they will write, as well as evaluating yng teachers do only assess the results of students' writing in general and briefly without regard to aspects such as imagination ratings poem, diction, and so on. The purpose of this study was to determine the ability to write poetry class V students of SDN 63 Pekanbaru. The research was conducted on the month in January 2016 to July 2016. The population in this study were all students of class V SD Negeri 63 Pekanbaru numbering 45. The sample in this research is using saturation sampling, in which members of the population used as a sample. The research instrument used in this study is to test the ability to write poetry writing poetry using descriptors votes. The data obtained in the ability to write poetry viewed from four aspects, namely diction, imagination, themes and rhymes. It can be concluded that students' ability to write poetry, there are five (11.11%) of students categorized very well, and 9 (20%) categorized as good, and 22 (48.89%) of students categorized fairly, while students who are less berkateogori no 9 ( 20%) students. Overall ability to write poetry class V students of SD Negeri 63 Pekanbaru obtain the average value of 64 categorized enough.